2012
DOI: 10.3109/17482968.2012.673172
|View full text |Cite
|
Sign up to set email alerts
|

REM behavior disorder associated with familial amyotrophic lateral sclerosis

Abstract: The association between RBD and synucleinopathies is well known. However, the association between RBD and other neuromuscular diseases has not been as well described. Our case study describes two siblings with familial ALS, confirmed by the identification of the L84F mutation in the SOD1 gene, and RDB. We hope this case study will promote future studies on the prevalence of this association and will stimulate research in identifying the underlying pathogenic mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…It is evident that in this family, females had a more severe form of the disease compared to males. It has been reported that, in the 50 affected members with ALS from 10 families from different populations (31)(32)(33)(34)(35)(36)(37) with the L84F substitution (c.255G4C), there was wide variation in age at onset (19-65 years) and duration of the disease (1.5-12 years). Unlike our family, there was no gender bias in the course of the disease.…”
Section: Discussionmentioning
confidence: 98%
“…It is evident that in this family, females had a more severe form of the disease compared to males. It has been reported that, in the 50 affected members with ALS from 10 families from different populations (31)(32)(33)(34)(35)(36)(37) with the L84F substitution (c.255G4C), there was wide variation in age at onset (19-65 years) and duration of the disease (1.5-12 years). Unlike our family, there was no gender bias in the course of the disease.…”
Section: Discussionmentioning
confidence: 98%
“…It has been often reported that patients with ALS may present difficulties initiating and maintaining sleep, reduced sleep efficiency, increased stage 1 sleep, and shortened duration of rapid eye movement (REM) sleep (6)(7)(8)(9)(10)(11)(12)14). In addition, with the exception of few single cases (14)(15)(16), motor activity during sleep that could be indicative of REM sleep behavior disorder (RBD) and REM sleep without atonia (RSWA), which are highly prevalent in other neurodegenerative disorders with brainstem involvement, has not been assessed. In addition, with the exception of few single cases (14)(15)(16), motor activity during sleep that could be indicative of REM sleep behavior disorder (RBD) and REM sleep without atonia (RSWA), which are highly prevalent in other neurodegenerative disorders with brainstem involvement, has not been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…These conditions, including Parkinson’s disease (PD), multiple system atrophy (MSA), dementia with Lewy bodies (DLB)(Gagnon et al 2006, Manni et al 2011), and pure autonomic failure (PAF)(Kaufmann et al 2017) are so named because of the characteristic intracellular protein accumulation of alpha-synuclein, that may be visualized in a subset of synucleinopathies (for example PD and DLB) as Lewy bodies (Figure 1)(Postuma et al 2009, Classen and Schnitzler 2010). It is unclear whether RBD is linked to the alpha-synucleinopathies via aggregated intracellular material, or through a common anatomic pathology(Ebben et al 2012). …”
Section: Introductionmentioning
confidence: 99%